HUBUNGAN PERSEPSI KESEHATAN DAN KESELAMATAN KERJA DENGAN KECELAKAAN KERJA PADA PEKERJA SAMPAH DI TPA BUKIT PINANG SAMARINDA - Siti Rahmawati (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2017)
The Ministry of Manpower of the Trans Center of Jakarta, the case of work-related injuries in Indonesia including the result of collecting garbage from January to September 2003 recorded 81,169 cases or more than 300 cases per day. This study aims to determine the correlation between occupational health and safety perception with work accident at garbage worker at TPA Bukit Pinang Samarinda. Using analytical survey method with Case Control design. Data analysis using Fisher Exact test (? = 5%.) The result of the research showed that there was correlation between perception of susceptibility with work accident (? = 0,042), no correlation between perception of severity with work accident (? = 0,614) prevention with work accident (? = 0,003), there was correlation between perception of obstacle with work accident (? = 0,019). Suggestions that can be given to the environmental agency are expected to increase the knowledge of worker health and safety. In addition, training needs to be done for workers about how to work safely and safely in an effort to reduce the incidence of accidents.